For better, for worse: the ethics of divorce after marriage equality - Williams, Natalie E. (Lexington Books/Fortress Academic, 2020)
Introduction: Why divorce matters now: origins of the U.S. "divorce crisis" -- The theo-ethical history of marriage and the U.S. divorce landscape -- Shame in the moral frameworks of marriage regulation -- Fetishizing the family: shame in Christian divorce doctrines -- U.S. divorce policies and "family values" rhetoric -- Queer resistance and gay assimiliation: marriage (and divorce) equality -- Resisting shame and reimagining family success.